Uticaj sociodemografskih karakteristika na desničarsku autoritarnost - Nikolov, Jelena (Specijalna edukacija i rehabilitacija, 2024)
Introduction. This paper explores the impact of sociodemographic characteristics on right-wing authoritarianism. Right-wing authoritarianism is defined as a combination of three attitudinal clusters: authoritarian submission, authoritarian aggression, and conventionalism. Objective. The aim of the study is to examine the influence of gender, age, education, and religiosity on right-wing authoritarianism. Methods. In the conducted research, right-wing authoritarianism was defined as the criterion variable, while others were specified as predictors. The Right-Wing Authoritarianism (RWA) scale, consisting of 12 questions and measured at an interval level, was used to assess right-wing authoritarianism. The study was conducted on 112 participants of different genders and ages from the general population in Serbia, using a non-random, voluntary sample. Results. The obtained data show that, on average, respondents exhibit a slightly more pronounced right-wing authoritarianism (both in terms of the overall scale and its subscales). There were gender differences in the degree of right-wing authoritarianism, with men being more authoritarian than women. Age-related differences in the degree of right-wing authoritarianism were found, as well as the fact that respondents with higher levels of education are less prone to authoritarianism, while those who emphasize their religiosity are more inclined toward authoritarianism. Conclusion. The results of this study have important implications for interventions to reduce the prevalence of rightwing authoritarianism and the development of policies to mitigate its negative effects on individuals and society. Based on the obtained results, implications for further research.